NARASI PETUALANGAN TOKOH DALAM PENCARIAN HURUF HIJAIYAH DALAM FILM SIRAJ CARTOON EPISODE 1-3 SEASON 1: KAJIAN NARATOLOGI TZVETAN TODOROV - Cahyani Wibowo, Aulia; Rohanda; Restu Pauji, Resa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the narrative structure of the characters’ adventures in the animated series Siraj Cartoon, episodes 1–3 of season 1, using Tzvetan Todorov’s narratological approach and Joseph Campbell’s Hero’s Journey theory. This study employs a qualitative descriptive method, with data consisting of dialogue, scenes, character actions, and the sequence of events depicted in the series. The analysis was conducted by identifying the narrative structure based on Todorov’s stages, which include equilibrium, disruption, recognition of disruption, attempt to repair the disruption, and reinstatement of equilibrium. Additionally, the characters’ journey in their search for the Hijaiyah letters was analyzed through the three stages of Joseph Campbell’s Hero’s Journey: departure, initiation, and return. The results of the study indicate that the film Siraj Cartoon constructs an adventure narrative through a shift from an initial state of equilibrium, the emergence of problems during the search for the Hijaiyah letters, the process of resolving the conflict, and the eventual attainment of a new equilibrium. The journeys of the characters Noura and Rashid demonstrate that the adventure in the film not only serves as a plot driver but also functions as a medium for learning the Hijaiyah alphabet through the experiences and challenges faced by the characters. Thus, Siraj Cartoon can be understood as an educational animated work that constructs the learning of the Hijaiyah alphabet through a systematic adventure narrative structure and character journeys.